Metaphors and Related Expressions in Older Adults in the Field of Trauma and Stress-related Disorders: A Scoping Review. (2nd January 2023) - Rossi, Sandra; Maercker, Andreas; Heim, Eva
ABSTRACT: A scoping review was conducted to explore the metaphors and related expressions older adults use to describe extremely stressful events that may lead to Post-Traumatic Stress Disorder (PTSD), Complex PTSD (CPTSD), Prolonged Grief Disorder (PGD), or Adjustment Disorder (AjD). Relevant databases from psychology, gerontology, and related fields were searched. In addition, relevant references found in included papers were considered. Inclusion criteria were: qualitative study, sample of older adults (age 65+), and focus on maladaptive rather than adaptive psychological aspects. Eleven studies focusing on PTSD, 5 on CPTSD, 13 on PGD, and 10 on AjD were included. Metaphors and other expressions related to extremely stressful events were then extracted and analyzed. Multiple linguistic expressions to describe extremely stressful events and stress-related symptoms were identified. Metaphors and related expressions often referred to the body and the theme of moving on with one's life.